ASSESSING THE NUTRITIONAL STATUS AND ASSOCIATED FACTORS AMONG SECONDARY SCHOOL STUDENTS IN CHU SE DISTRICT, GIA LAI PROVINCE, VIETNAM: A CROSS-SECTIONAL STUDY (Tạp chí Y học Cộng đồng, 2026)
Undernutrition and obesity are prevalent nutritional issues among adolescents. This cross-sectional study aimed to evaluate the nutritional status and associated factors among secondary school students in Chu Se district, Gia Lai province. Participants were selected using a stratified random sampling method. Data collection included using a structured questionnaire based on the Global School-based Student Health Survey and Physical Activity Ǫuestionnaire for Older Children questionnaire, and students' height and weight were measured directly using a tape measure and a digital scale. Undernutrition and obesity were determined using the WHO AnthroPlus software. Multivariable logistic regression analysis was employed to explore associations, with statistical significance set at p
Keywords: Stunting, wasting, overweight, obesity, adolescent.